2017
DOI: 10.1523/jneurosci.3929-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Triple-Flash Illusion Reveals a Driving Role of Alpha-Band Reverberations in Visual Perception

Abstract: The modulatory role of spontaneous brain oscillations on perception of threshold-level stimuli is well established. Here, we provide evidence that alpha-band (∼10 Hz) oscillations not only modulate perception of threshold-level sensory inputs but also can drive perception and generate percepts without a physical stimulus being present. We used the "triple-flash" illusion: Occasional perception of three flashes when only two spatially coincident veridical ones, separated by ∼100 ms, are presented. The illusion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 58 publications
5
19
0
Order By: Relevance
“…These studies have consistently shown that lower alpha amplitude prior to stimulus onset predicts increased likelihood of the stimulus being perceived (e.g., Ergenoglu et al ., 2004; Babiloni et al ., 2006; Hanslmayr et al ., 2007; van Dijk et al ., 2008; Romei et al ., 2010; MacLean & Arnell, 2011; Limbach & Corballis, 2016; Iemi et al ., 2017). Lower alpha power also increases the likelihood of perceiving a stimulus when no stimulus is presented, both in terms of false positives (Limbach & Corballis, 2016; Iemi et al ., 2017), and visual illusions (Lange et al ., 2013; Cecere et al ., 2015; Gulbinaite et al ., 2017), consistent with alpha's role in spatial gain modulation. These studies and others have supported the conclusion that alpha oscillations are a key mechanism underlying the effects of spatial attention (Jensen & Mazaheri, 2010).…”
Section: Discussionsupporting
confidence: 54%
“…These studies have consistently shown that lower alpha amplitude prior to stimulus onset predicts increased likelihood of the stimulus being perceived (e.g., Ergenoglu et al ., 2004; Babiloni et al ., 2006; Hanslmayr et al ., 2007; van Dijk et al ., 2008; Romei et al ., 2010; MacLean & Arnell, 2011; Limbach & Corballis, 2016; Iemi et al ., 2017). Lower alpha power also increases the likelihood of perceiving a stimulus when no stimulus is presented, both in terms of false positives (Limbach & Corballis, 2016; Iemi et al ., 2017), and visual illusions (Lange et al ., 2013; Cecere et al ., 2015; Gulbinaite et al ., 2017), consistent with alpha's role in spatial gain modulation. These studies and others have supported the conclusion that alpha oscillations are a key mechanism underlying the effects of spatial attention (Jensen & Mazaheri, 2010).…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies investigating prestimulus oscillatory activity in double flash illusions using MEG have found that crossmodal influence is associated with increased beta band power (13–21 Hz) in left temporal areas 18 ; enhanced excitability in visual areas, as reflected by decreased alpha band power; and increased gamma band power in a more extensive cortical network including temporal areas 19 . Prestimulus alpha band power is also decreased in the triple flash illusion, where two rapidly presented flashes are occasionally perceived as three 23 . Interestingly, the optimal delay between flashes is correlated with the subject-specific impulse response frequency, pointing to a contribution of oscillatory reverberation to illusory visual perception.…”
Section: Discussionmentioning
confidence: 99%
“…Their results revealed a large alpha oscillation that begins after the ERP-like early response and is sustained for lags up to >1 s. This component, the perceptual echo, represents the rhythmicity that the visual system naturally selects from the random sequence. Recent studies have demonstrated that the echo response may be employed as a mechanism of active rhythmic sampling that can be modulated according to current visual demand ( Gulbinaite et al. 2017 ; Benedetto et al.…”
Section: Introductionmentioning
confidence: 99%